(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the geoecological foundations for implementing the Kunming-Montreal Global Biodiversity Framework in Uzbekistan in the context of "The Great Acceleration" – global anthropogenic changes that began in the second half of the 20th century. The article discusses the degradation of biological and landscape diversity, the need to expand the network of protected natural areas (PNAs), the concept of ecological networks, and their connectivity level. The current state of PNAs in Uzbekistan, particularly in the Fergana Valley, their territorial coverage, the Species Protection Index (SPI), and opportunities to achieve global goals (30% coverage by 2030) are examined based on scientific research and analyses. Based on the obtained results, recommendations are provided for increasing the area of PNAs, ensuring connectivity through ecological corridors, enhancing management efficiency, and improving national strategies. The article serves to adapt Uzbekistan’s environmental policy to green development and global changes.